Collaborative Pentahelix Model in Developing Quality Family Village Programs (Universitas Pendidikan Indonesia (UPI), 2025)
The population is increasing, of course if it is not controlled it will become a problem in itself, with the existence of KB villages in each region being one of the efforts to reduce the population. This study aims to determine the collaboration of the pentahelix model in developing KB villages in Ciamis district. The research approach used is qualitative with a case study method, the data collection techniques used are interviews, observation and documentation. The results of this study are that the pentahelix model involves government academics, industry, community and media in a joint effort to increase the effectiveness of the kampung kb program in Padamulya village. Each stakeholder has a contribution in planning, implementing and evaluating the KB village program. Pentahelix collaboration can increase community participation, knowledge and awareness of the importance of family planning in Padamulya Village. Positive impacts can also be seen in changes in community behavior related to the use of contraceptives, awareness of clean and healthy living, close relationships within the family, improvement of the community's economy, concern for the environment, activeness of youth through PIK-R activities and others. This collaboration also ensures the integration of resources from various sectors, creating a holistic, sustainable, and sustainable development-oriented KB village program in Padamulya Village to finally get achievements at the West Java provincial level.